(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
Family farmers are alternatives for sustainable development. The aim was to analyze socioeconomic factors of subsistence family farming and the promotion of agrotourism in the rural area of Florencia Caquetá. The study is quantitative, descriptive and transactional. The sample consisted of 46 units. The connection between family farming and territory, agricultural activities and agrotourism, capacity profile and attitude profile were evidenced. It was found that there are several socioeconomic factors, including access to land, use profile, attitude profile: public policies, institutional support, training, sustainable agricultural activities, etc.